2014
DOI: 10.1177/1046496414530789
|View full text |Cite
|
Sign up to set email alerts
|

Conflict and Creativity in Interdisciplinary Teams

Abstract: International audienceWe examine the effects of conflict and conflict asymmetry on creativity in interdisciplinary teams. Testing our hypotheses on teams working on graduate-level nanobiotechnology projects, we found task conflict to have a positive relationship with creativity whereas relationship conflict had a negative relationship with creativity. Our results also revealed that relationship conflict asymmetry had a positive effect on creativity. Examining the two components of creativity separately, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 52 publications
4
80
1
4
Order By: Relevance
“…Ancona and Caldwell (1992) found that teams with different functional backgrounds engage in more outside communication, and are rated as more innovative. In science, there is evidence that field variety improves scientific creativity (Hollingsworth, 2006;Rafols and Meyer, 2010;Yong et al, 2014). For example, Hollingsworth argued that scientific organizations that generate many breakthrough discoveries in biomedical research are characterized by moderately high levels of field variety, as well as organizational structures that facilitate cross-field communication and integration of ideas.…”
Section: Variety and Noveltymentioning
confidence: 97%
See 1 more Smart Citation
“…Ancona and Caldwell (1992) found that teams with different functional backgrounds engage in more outside communication, and are rated as more innovative. In science, there is evidence that field variety improves scientific creativity (Hollingsworth, 2006;Rafols and Meyer, 2010;Yong et al, 2014). For example, Hollingsworth argued that scientific organizations that generate many breakthrough discoveries in biomedical research are characterized by moderately high levels of field variety, as well as organizational structures that facilitate cross-field communication and integration of ideas.…”
Section: Variety and Noveltymentioning
confidence: 97%
“…We argue that although creativity is composed of the novelty of the outcome and its impact, those are distinct concepts having their own causal relationships (Yong et al, 2014). More novel papers and patents which explore new combinations of knowledge space, carry a research stream into more unknown territory, or use a large number of knowledge domains may have high impact (Newman and Cooper, 1993;Schoenmakers and Duysters, 2010), while some contrary studies showed that patents that use unusual reference profiles or draw from distinct knowledge sources do not have high impact (Dahlin and Behrens, 2005;Nemet and Johnson, 2012).…”
Section: Creativity In Sciencementioning
confidence: 99%
“…Closer to our work are the research of Girotra, Terwiesch, and Ulrich (2010) in search of outstanding (disruptive) ideas, Yong, Sauer, and Mannix (2014) in analysing how creativity is related to the composition and work environment of teams, Goldenberg, Mazursky and Solomon (1999) in generating ideas for new products through lateral thinking and other methods, and Eppler, Hoffman and Bresciani (2011) in using different tools to generate new business models.…”
Section: 1-experimentation In the Business Model Innovation Fieldmentioning
confidence: 99%
“…En su opinión, "para la mayor parte de los retos relacionados con la innovación, una organización preferirá 99 malas ideas y una idea sobresaliente a cien ideas simplemente buenas" ((Girotra et al, 2010), pág. 591).Pensemos por ejemplo en la búsqueda de un producto con el que pretendemos ganar una batalla de estándares, o en un modelo de negocio capaz de crear un mercado. Yong, Sauer y Mannix recurren también a la experimentación para analizar cómo la creatividad se ve influenciada por diversos factores relativos a la composición de y ambiente de los equipos en que se genera esa creatividad (Yong et al, 2014). El encargo a los equipos que participan en el experimento es en este caso el diseño de 140 productos nanobiotecnológicos.…”
unclassified
“… Yong, Sauer y Mannix recurren también a la experimentación para analizar cómo la creatividad se ve influenciada por diversos factores relativos a la composición de y ambiente de los equipos en que se genera esa creatividad (Yong et al, 2014). El encargo a los equipos que participan en el experimento es en este caso el diseño de 140 productos nanobiotecnológicos.…”
unclassified